Green Human Resource Management on Green Behavior Mediated by Green Work Engagement Among Rejang Lebong Hospital - Hani, Nessa Aulia; Praningrum, Praningrum (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Human resource management refers to the strategies and practises implemented by an organisation to effectively oversee and nurture its personnel, enabling them to effectively accomplish the organization's objectives and mission. The aim of this research is to investigate the relationship between Green Human Resource Management and Green Behavior, which is then explored with the role of Green Work Engagement as a mediator. This research uses an explanatory method. The data collection method was carried out through distributing questionnaires involving all 300 Rejang Lebong Regional Hospital employees. In addition, this research uses a non-probability sampling method, namely the number of samples is adjusted to the population size. The testing steps start from testing validity, reliability, direct influence hypothesis, mediation effect hypothesis, and finally cross-loading. The study's findings indicate that (1) Rejang Lebong Hospital's employee green behavior has improved significantly since implementing green human resource management (2) Green work engagement has a positive and significant impact on employee green behavior at Rejang Lebong Hospital (3) Rejang Lebong Hospital's green work engagement is significantly influenced for the better by the hospital's green human resource management (4) Green human resource management has a big and positive impact on employee green behavior at Rejang Lebong Hospital. This influence is mediated by the green work engagement have towards environmentally conscious work practises.